Long‐term changes in occurrence, relative abundance, and reproductive fitness of bat species in relation to arrival of White‐nose Syndrome in West Virginia, USA. Issue 18 (4th August 2021) - Johnson, Catherine; Brown, Donald J.; Sanders, Chris; Stihler, Craig W.
Abstract: White‐nose syndrome (WNS) is a disease caused by the fungus  Pseudogymnoascus destructans  which has resulted in the deaths of millions of bats across eastern North America. To date, hibernacula counts have been the predominant means of tracking the spread and impact of this disease on bat populations. However, an understanding of the impacts of WNS on demographic parameters outside the winter season is critical to conservation and recovery of bat populations impacted by this disease. We used long‐term monitoring data to examine WNS‐related impacts to summer populations in West Virginia, where WNS has been documented since 2009. Using capture data from 290 mist‐net sites surveyed from 2003 to 2019 on the Monongahela National Forest, we estimated temporal patterns in presence and relative abundance for each bat species. For species that exhibited a population‐level response to WNS, we investigated post‐WNS changes in adult female reproductive state and body mass. Myotis lucifugus (little brown bat), M . septentrionalis (northern long‐eared bat), and Perimyotis subflavus (tri‐colored bat) all showed significant decreases in presence and relative abundance during and following the introduction of WNS, while  Eptesicus fuscus (big brown bat) and Lasiurus borealis (eastern red bat) responded positively during the WNS invasion. Probability of being reproductively active was not significantly different for any species, though a shift to earlier reproduction was estimated for E . fuscus and M . septentrionalis . For some species, body mass appeared to be influenced by the WNS invasion, but the response differed by species and reproductive state. Results suggest that continued long‐term monitoring studies, additional research into impacts of this disease on the fitness of WNS survivors, and a focus on providing optimal nonwintering habitat may be valuable strategies for assessing and promoting recovery of WNS‐affected bat populations. Abstract : We used long‐term monitoring data to examine impacts from white‐nose syndrome on summer bat populations in West Virginia. The little brown bat, northern long‐eared bat, and tri‐colored bat all showed significant decreases in survey presence and relative abundance during and following the introduction of WNS, while the big brown bat and eastern red bat responded positively to the WNS invasion. We also investigate post‐WNS changes in adult female reproduction and body mass for those species in the study area.